Seismic performance of water tank tower - Ismail, Fadrul Hafiz (2009)
A water tower consists of an elevated water tank and a shaft. Purpose of water tank tower is storage of a certain quantity of water at sufficient pressure for transporting water over certain distance. Water tower’s design should be able to resists lateral load if earthquake occurs. Earthquake is a sudden movement of the earth caused by the abrupt release of strain that has accumulate over a long time. This dynamic vibration of lateral movement affects structures strength and behaviors. Thus, this study is based on seismic performance of water tank tower structure during earthquake and the objective is to determine the behavior of structure using computer software. Scope of this study is seismic performance effect on water tank tower around Malaysian region due to the nearest earthquake loading. The tower will be design and analyze using SAP 2000 and will produce structure behaviors according to the maximum earthquake loading. The findings and result analysis gained from this study can be use as reference, and be researched further focusing on improved design of water tank tower and less structure damage can be expected when earthquake loading occurs.